Les emprises militaires dans l’urbanisme grenoblois du XXe siècle : des opportunités foncières au patrimoine paysager - Philippe Grandvoinnet (In Situ)
Grenoble ceased to be qualified as 'place forte' [fortified town] in 1925, and the town's subsequent urban development was largely conditioned by the availability of former military properties. Considered at first as simple real estate opportunities, these military structures were gradually invested with historical and cultural values which feature strongly in certain operations of urban development and landscaping. Starting out from this example at Grenoble, we will try to assess the impact of military installations of the seventeenth to nineteenth centuries on the town-planning of the twentieth century and will map this now recognised heritage in its urban context.